2018
DOI: 10.1039/c8fo01331d
|View full text |Cite
|
Sign up to set email alerts
|

Viability of microencapsulated Akkermansia muciniphila and Lactobacillus plantarum during freeze-drying, storage and in vitro simulated upper gastrointestinal tract passage

Abstract: Microencapsulated and subsequently freeze-dried cells showed acceptable storage stability and enhanced survival during in vitro upper gastrointestinal tract passage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…A number of studies have shown that the viability of probiotics can be improved by embedding them within microgels or other types of microcapsules (Gonzalez‐Ferrero et al., ; Lee, Ji, Lee, Choi, & Cho, ; Marcial‐Coba et al., ; Mawad, Helmy, Shalkami, Kathayat, & Rajashekara, ; Mirtic et al., ; Tiani, Yeung, McClements, & Sela, ; Yao et al., ; Yeung et al., ; Yeung, Ucok, Tiani, McClements, & Sela, ). Typically, these particles have dimensions that fall within the 1 to 1,000 μm range.…”
Section: Microencapsulation Of Probioticsmentioning
confidence: 99%
“…A number of studies have shown that the viability of probiotics can be improved by embedding them within microgels or other types of microcapsules (Gonzalez‐Ferrero et al., ; Lee, Ji, Lee, Choi, & Cho, ; Marcial‐Coba et al., ; Mawad, Helmy, Shalkami, Kathayat, & Rajashekara, ; Mirtic et al., ; Tiani, Yeung, McClements, & Sela, ; Yao et al., ; Yeung et al., ; Yeung, Ucok, Tiani, McClements, & Sela, ). Typically, these particles have dimensions that fall within the 1 to 1,000 μm range.…”
Section: Microencapsulation Of Probioticsmentioning
confidence: 99%
“…Interestingly, the potential temperature effect associated with an oxygen exposure can be further assessed in data pertaining to the strategies explored to successfully protect and deliver viable functional A. muciniphila cells, which have been focused mainly on encapsulation systems. According to Marcial-Coba et al (2018, 2019b, the stability displayed when assessing different microencapsulation formulations was higher at refrigeration temperatures (4 • C). The researchers described two microencapsulation protocols based on conventional extrusion mechanism [ionotropic crosslinking biopolymer in hardening solution containing cations like Ca 2+ (de Prisco et al, 2015)] using A. muciniphila strain DSM22959.…”
Section: Akkermansiamentioning
confidence: 99%
“…The researchers described two microencapsulation protocols based on conventional extrusion mechanism [ionotropic crosslinking biopolymer in hardening solution containing cations like Ca 2+ (de Prisco et al, 2015)] using A. muciniphila strain DSM22959. In the first study the authors reported the application of xanthan/gellan gum polymeric matrix for cell immobilization with a subsequent freeze-drying step, in which they used various combinations of cryoprotective compounds (Marcial-Coba et al, 2018). The use of higher sugar cryoprotectants [sweetener agave syrup 10 % (w/v)] combined with xanthan/gellan gum matrix, in the form of freeze-dried microcapsules, provided a higher encapsulation efficiency (EE) (76.2%) when compared with the other cryoprotectants.…”
Section: Akkermansiamentioning
confidence: 99%
“…While most of the canonical probiotic bacteria can tolerate and even use some oxygen, most of the next-generation therapeutic bacteria are strict anaerobes. Hence, the encapsulation and viable delivery of these may be pivotal (Marcial-Coba et al, 2018;van der Ark et al, 2017a).…”
Section: Market Development and Production Of Health-promoting Bacteriamentioning
confidence: 99%